De novo Transcriptome Analysis of Rhizoctonia solani AG1 IA Strain Early Invasion in Zoysia japonica Root - Zhu, Chen; Ai, Lin; Wang, Li; Yin, Pingping; Liu, Chenglan; Li, Shanshan; Zeng, Huiming (Frontiers in Microbiology, 2016)
Zoysia japonica brown spot was caused by necrotrophic fungus Rhizoctonia solani invasion, which led to severe financial loss in city lawn and golf ground maintenance. However, little was known about the molecular mechanism of Rhizoctonia solani pathogenicity in Zoysia japonica. In this study we examined early stage interaction between Rhizoctonia solani AG1 IA strain and Zoysia japonica cultivar “Zenith” root by cell ultra-structure analysis, pathogenesis-related proteins assay and transcriptome analysis to explore molecular clues for AG1 IA strain pathogenicity in Zoysia japonica. No obvious cell structure damage was found in infected roots and most pathogenesis-related protein activities showedg a downward trend especially in 36h post inoculation, which exhibits AG1 IA strain stealthy invasion characteristic. According to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) database classification, most DEGs in infected “Zenith” roots dynamically changed especially in 3 aspects, signal transduction, gene translation and protein synthesis. Total 3422 unigenes of “Zenith” root were predicted into 14 kinds of resistance (R) gene class. Potential fungal resistance related unigenes of “Zenith” root were involved in ligin biosynthesis, phytoalexin synthesis, oxidative burst, wax biosynthesis, while two down-regulated unigenes encoding leucine-rich repeat receptor protein kinase and subtilisin-like protease might be important for host-derived signal perception to AG1 IA strain invasion. According to Pathogen Host Interaction (PHI) database annotation, 1508 unigenes of AG1 IA strain were predicted and classified into 37 known pathogen species, in addition, unigenes encoding virulence, signaling, host stress tolerance and potential effector were also predicted. This research uncovered transcriptional profiling during the early phase interaction between Rhizoctonia solani AG1 IA strain and Zoysia japonica, and will greatly help identify key pathogenicity of AG1 IA strain.